2006
DOI: 10.1523/jneurosci.2615-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Impairs CNS Remyelination by Inhibiting Oligodendrocyte Precursor Cell Differentiation

Abstract: Demyelination in the adult CNS can be followed by extensive repair. However, in multiple sclerosis, the differentiation of oligodendrocyte lineage cells present in demyelinated lesions is often inhibited by unknown factors. In this study, we test whether myelin debris, a feature of demyelinated lesions and an in vitro inhibitor of oligodendrocyte precursor differentiation, affects remyelination efficiency. Focal demyelinating lesions were created in the adult rat brainstem, and the naturally generated myelin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
583
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 675 publications
(602 citation statements)
references
References 30 publications
10
583
0
9
Order By: Relevance
“…Using heterochronic parabiosis (Villeda et al 2011) in a toxin-induced focal demyelination model of mouse spinal cord, Ruckh et al demonstrated improvements in the remyelination of aged brains mediated by endogenous OPCs whose differentiation capacity was restored by exposing them to a youthful systemic environment. Considering previous hypotheses about the role of the innate immune system in remyelination (Kotter et al 2006), these results support the idea that young macrophages recruited during remyelination facilitate OPC differentiation by removing inhibitory myelin debris (Ruckh et al 2012).…”
Section: Remyelination and Agingsupporting
confidence: 88%
“…Using heterochronic parabiosis (Villeda et al 2011) in a toxin-induced focal demyelination model of mouse spinal cord, Ruckh et al demonstrated improvements in the remyelination of aged brains mediated by endogenous OPCs whose differentiation capacity was restored by exposing them to a youthful systemic environment. Considering previous hypotheses about the role of the innate immune system in remyelination (Kotter et al 2006), these results support the idea that young macrophages recruited during remyelination facilitate OPC differentiation by removing inhibitory myelin debris (Ruckh et al 2012).…”
Section: Remyelination and Agingsupporting
confidence: 88%
“…[72][73][74] Furthermore, myelin debris itself inhibits remyelination via inhibition of OPC differentiation. 74,75 The results show that the increase in oligodendrogenesis is linked to increased proliferation of the NG2 ϩ OPC population and to morphologic changes specific to the T PLP mice. Although proliferation is a characteristic feature of OPC activation, 14,16,76 these cells also respond by changing their structure and level of expression of NG2.…”
Section: Discussionmentioning
confidence: 93%
“…One possibility is that the emergence of the remyelination-supportive microglia phenotype is causally linked to one of the prototypical microglia effector functions, namely phagocytosis. Undoubtedly, clearance of tissue debris is indispensable for regeneration to occur (Kotter et al, 2006). Nonetheless, it has been shown that phagocytosis of apoptotic cells and myelin debris renders microglia/ macrophages supportive of regenerative processes (Bechmann et al, 2001;Boven et al, 2006;Savill et al, 2002).…”
Section: Discussionmentioning
confidence: 99%